VIP2 in LNGS - Testing the Pauli Exclusion Principle for electrons with high sensitivity. (September 2019) - Marton, J.; Pichler, A.; Amirkhani, A.; Bartalucci, S.; Bazzi, M.; Bertolucci, S.; Bragadireanu, M.; Cargnelli, M.; Clozza, A.; Curceanu, C.; Del Grande, R.; De Paolis, L.; et al.
Abstract: The VIP2 (VIolation of the Pauli Exclusion Principle) experiment at the Gran Sasso underground laboratory (LNGS) is searching for possible violations of standard quantum mechanics predictions in atoms at very high sensitivity. We investigate atomic transitions with precision X-ray spectroscopy in order to test the Pauli Exclusion Principle (PEP) and therefore the related spin-statistics theorem. We will present our experimental method for the search for "anomalous" (i.e. Pauli-forbidden) X-ray transitions in copper atoms, produced by "new" electrons, which could have tiny probability to undergo Pauli-forbidden transition to the ground state already occupied by two electrons. We will describe the VIP2 experimental setup, which is taking data at LNGS presently. The goal of VIP2 is to test the PEP for electrons with unprecedented accuracy, down to a limit in the probability that PEP is violated at the level of 10 −31 . We will present current experimental results and discuss implications of a possible violation.